CLINICAL AND PATHOGENETIC ASPECTS OF NUTRITIONAL DISORDERS IN YOUNG CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Nutritional disorders in young children develop on the basis of complex pathogenetic mechanisms arising from physiological immaturity of the organism. The article scientifically analyzes morphofunctional features of the digestive tract, maturation processes of enzymatic systems, neurohumoral regulation mechanisms and the role of intestinal microbiota. Clinical syndromes are pathogenetically substantiated with their age-specific course characteristics demonstrated. Based on research findings, practical directions for diagnostics and prophylaxis are proposed.